Comparative, Prospective, Case–Control Study of Open versus Laparoscopic Pyeloplasty in Children with Ureteropelvic Junction Obstruction: Long-term Results - Piaggio, Lisandro A.; Corbetta, Juan P.; Weller, Santiago; Dingevan, Ricardo Augusto; Duran, Víctor; Ruiz, Javier; Lopez, Juan C. (Frontiers in Pediatrics, 2017)
INTRODUCTION: We compare open pyeloplasty (OP) versus laparoscopic pyeloplasty (LP) in children in a multicenter, prospective, case control study. MATERIAL AND METHODS: From May 2007 to March 2009, a program was established at Hospital Garrahan, the reference center, to perform LP with a mentoring surgeon that would attend the institution once a month. Every new case of UPJO diagnosed in the reference institution was offered to participate in the study. If the patient was enrolled, it was scheduled for LP. The following patient diagnosed with UPJO was operated on with open technique and served as a case control. In three other facilities patients were only offered LP and had a matched control open case at the reference institution. The first end point of the study was patient recovery: analgesia requirement and length of hospitalization (LOH). The second end point of the study was resolution of UPJO in long-term follow-up for the two techniques. Demographic data, surgical time, perioperative complications, analgesia requirement, analgesia score during hospitalization, length of hospitalization and outcome were recorded. Both groups received the same postoperative indications for pain control. Parents were asked to assess pain in their children every 4 hours postoperatively and to complete a pain scale chart to which the nurses were blinded. RESULTS: 15 OP and 15 LP were compared. Groups were similar with regard to sex, age, weight and laterality. Mean surgical time was longer in LP than in OP group (mean 188 vs 65 minutes) (p < .01). Hospitalization was shorter for LP group with a mean of 1.9 vs 2.5 days for OP group (p < .05).Postoperative analgesia requirement was significantly higher in the OP group with a mean use of morphine of 1.7 mg/kg vs 0.06 mg/kg in the LP group (p < .05). Pain scores were similar in both groups. At a mean follow-up of 58 months there were no failures. CONCLUSIONS: In this prospective comparative cohort, LP was a longer procedure than OP. Both procedures had the same efficacy and complication rates, but patients undergoing LP needed fewer narcotics for pain control and had a shorter hospitalization.